Influences of phase transition and microstructure on dielectric properties of Bi0.5Na0.5Zr1-xTixO3 ceramics - Jaiban P. (2014)
ABSTRACT: Bismuth sodium zirconate titanate ceramics with the formula Bi0.5Na0.5Zr1-xTixO3 [BNZT], where x = 0.3, 0.4, 0.5, and 0.6, were prepared by a conventional solid-state sintering method. Phase identification was investigated using an X-ray diffraction technique. All compositions exhibited complete solubility of Ti4+ at the Zr4+ site. Both a decrease of unit cell size and phase transition from an orthorhombic Zr-rich composition to a rhombohedral crystal structure in a Ti-rich composition were observed as a result of Ti4+ substitution. These changes caused dielectric properties of BNZT ceramics to enhance. Microstructural observation carried out employing SEM showed that average grain size decreased when addition of Ti increased. Grain size difference of BNZT above 0.4 mole fraction of Ti4+ displayed a significant increase of dielectric constant at room temperature.